Musculoskeletal ultrasound in hemophilia: Results and recommendations from a global survey and consensus meeting. Issue 5 (10th July 2021) - Bakeer, Nihal; Dover, Saunya; Babyn, Paul; Feldman, Brian M.; von Drygalski, Annette; Doria, Andrea S.; Ignas, Danial M.; Abad, Audrey; Bailey, Cindy; Beggs, Ian; Chang, Eric Y.; Dunn, Amy; et al.
Abstract: Introduction: For persons with hemophilia, optimization of joint outcomes is an important unmet need. The aim of this initiative was to determine use of ultrasound in evaluating arthropathy in persons with hemophilia, and to move toward consensus among hemophilia care providers regarding the preferred ultrasound protocols for global adaptation. Methods: A global survey of hemophilia treatment centers was conducted that focused on understanding how and why ultrasound was being used and endeavored to move toward consensus definitions of both point‐of‐care musculoskeletal ultrasound (POC‐MSKUS) and full diagnostic ultrasound, terminology to describe structures being assessed by ultrasound, and how these assessments should be interpreted. Next, an in‐person meeting of an international group of hemophilia health care professionals and patient representatives was held, with the objective of achieving consensus regarding the acquisition and interpretation of POC‐MSKUS and full diagnostic ultrasound for use in the assessment of musculoskeletal (MSK) pathologies in persons with hemophilia. Results: The recommendations were that clear definitions of the types of ultrasound examinations should be adopted and that a standardized ultrasound scoring/measurement system should be developed, tested, and implemented. The scoring/measurement system should be tiered to allow for a range of complexity yet maintain the ability for comparison across levels. Conclusion: Ultrasound is an evolving technology increasingly used for the assessment of MSK outcomes in persons with hemophilia. As adoption increases globally for clinical care and research, it will become increasingly important to establish clear guidelines for image acquisition, interpretation, and reporting to ensure accuracy, consistency, and comparability across groups.